2022
DOI: 10.1111/cen.14795
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of treatment in differentiated thyroid cancer according to recommendations in current Dutch and American guidelines

Abstract: Objective: Assessment of treatment outcome in current de-escalation for differentiated thyroid cancer (DTC) according to the 2015 Dutch thyroid cancer guidelines and American Thyroid Association guidelines (ATA-15).Design: Retrospectively, the recommendations of the NL-15 and ATA-15 guidelines were evaluated to estimate potentially adequate, under-and overtreatment of DTC in patients treated in the University Medical Center Groningen between 2007 and 2017.Patients: A total of 240 patients with a cT1-T3aN0-1aM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Although the proposed risk stratification systems for recurrence prediction from countries other than Japan rely on a common set of clinicopathologic features [11][12][13], there are some differences in the specific definitions of the risk categories between the systems. Previous studies reported some risk stratification or management comparisons between the ATA and other associations [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the proposed risk stratification systems for recurrence prediction from countries other than Japan rely on a common set of clinicopathologic features [11][12][13], there are some differences in the specific definitions of the risk categories between the systems. Previous studies reported some risk stratification or management comparisons between the ATA and other associations [14,15].…”
Section: Introductionmentioning
confidence: 99%